2012
DOI: 10.1186/1745-6215-13-73
|View full text |Cite
|
Sign up to set email alerts
|

A multi-element psychosocial intervention for early psychosis (GET UP PIANO TRIAL) conducted in a catchment area of 10 million inhabitants: study protocol for a pragmatic cluster randomized controlled trial

Abstract: BackgroundMulti-element interventions for first-episode psychosis (FEP) are promising, but have mostly been conducted in non-epidemiologically representative samples, thereby raising the risk of underestimating the complexities involved in treating FEP in ‘real-world’ services.Methods/DesignThe Psychosis early Intervention and Assessment of Needs and Outcome (PIANO) trial is part of a larger research program (Genetics, Endophenotypes and Treatment: Understanding early Psychosis - GET UP) which aims to compare,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 63 publications
(76 reference statements)
0
41
0
Order By: Relevance
“…In September 2012, after being involved in the GET-UP trial (that was a study protocol aimed to evaluate the 9-month effectiveness and the feasibility in real-world routine clinical settings of an EIPbased multicomponent psychosocial intervention compared with Treatment As Usual [TAU] in a large cohort of FEP patients recruited from a 10 million inhabitant catchment area) (Ruggeri et al, 2012), the General Direction of the Emilia-Romagna Health Care Service financed a regional project (the "Progetto Regionale Esordi Psicotici"…”
Section: Eip In Italymentioning
confidence: 99%
See 1 more Smart Citation
“…In September 2012, after being involved in the GET-UP trial (that was a study protocol aimed to evaluate the 9-month effectiveness and the feasibility in real-world routine clinical settings of an EIPbased multicomponent psychosocial intervention compared with Treatment As Usual [TAU] in a large cohort of FEP patients recruited from a 10 million inhabitant catchment area) (Ruggeri et al, 2012), the General Direction of the Emilia-Romagna Health Care Service financed a regional project (the "Progetto Regionale Esordi Psicotici"…”
Section: Eip In Italymentioning
confidence: 99%
“…In September 2012, after being involved in the GET‐UP trial (that was a study protocol aimed to evaluate the 9‐month effectiveness and the feasibility in real‐world routine clinical settings of an EIP‐based multicomponent psychosocial intervention compared with Treatment As Usual [TAU] in a large cohort of FEP patients recruited from a 10 million inhabitant catchment area) (Ruggeri et al, ), the General Direction of the Emilia‐Romagna Health Care Service financed a regional project (the “Progetto Regionale Esordi Psicotici” [PREP]) with the aim of implementing innovative protocols of intervention based on the EIP model within all the Emilia Romagna Departments of Mental Health (Raballo et al, ). Specifically, main objectives of this project were: (a) to train the professional staff of each regional department of mental health on the theoretical and operational cores of the EIP model, and (b) to established a specialized EIP program within all departments, aimed to the assessment, diagnosis and treatment of FEP patients according to well‐defined, state‐of‐art guidelines on the topic (Regione Emilia Romagna, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such programs have been widely implemented over the last 20 years (McGorry, Edwards, Mihalopoulos, Harrigan, & Jackson, ). Several large randomized controlled studies of programs in different health care systems have demonstrated improved outcomes across several domains compared with treatment as usual (Kane et al, ; Petersen, Jeppesen et al, ; Ruggeri et al, ). The programs that have been tested in randomized controlled studies have a number of common components which have been identified through a process of systematic review and consensus (Addington, Mckenzie, Norman, Wang, & Bond, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this assumption, clinical syndromes may be viewed as the result of multiple interactions between different and quite distinct psychopathological dimensions (Keshavan, Tandon, Boutros, & Nasrallah, 2008;Tandon, Nasrallah, & Keshavan, 2009 (Eaton, Thara, Federman, Melton, & Liang, 1995;Marchesi et al, 2015). Likewise, institutionalization, long-term neuroleptic therapy, illness duration and ageing may contribute to shape both clinical presentation and outcome (McGorry et al, 1998;Ruggeri et al, 2012;Marchesi et al, 2015). As the early stages of psychosis are not affected by long-term confounding factors (Langeveld et al, 2013), first episode psychotic patients may represent a particularly useful study population where to better explore clinical expression of the core symptoms of psychoses.…”
mentioning
confidence: 99%